Evaluation of Condition Assessment of Tunnel Lining using Inspection Manual of CIRIA and FHWA - Usman F.; Banuar N.; Ismail M.N.; Othman N.A. (Institute of Physics Publishing, 2023)
Hydroelectric power; Hydroelectric power plants; Shotcreting; Variable speed transmissions; Condition assessments; Hydroelectric power station; Visual condition; Linings